A partition of the combined impacts of socioeconomic development and climate variation on economic risks of riverine floods. (25th November 2018) - Feng, Youcan; Rakowski, Cynthia L.; McPherson, Timothy N.; Judi, David R.
Abstract : Nonstationarities in both climate and socioeconomic systems play a role in flood risk. Based on a data‐driven case study in an urbanised watershed subjected to nonstationary factors in climate (rain, snow, and rain on snow) and socioeconomic conditions (e.g., built environment market changes), a multiscale, multimodel approach was adopted to develop local‐scale flood hazard predictions and an analytical framework was developed to quantify the associated flood risk. The case study shows that socioeconomic development can have a comparable contribution as climate variability when evaluating the expected annual damage. The relative contributions from socioeconomic development, in some cases, do not necessarily compound the risk, but can, in fact, act as a mitigating factor in annualised risk. Timelines of risk management planning are an important factor to consider. Socioeconomic factors such as market value can produce nonlinear and reversed trends in flood impact assessments within the 10‐year time frame. Furthermore, the nonstationarity of climate and development conditions together was shown to cause up to 43% of the variation in risk estimates and up to 70% of the variation in the benefit–cost effectiveness.